CARBON MONOXIDE-INDUCED UTERINE DAMAGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Carbon monoxide (CO) is one of the most common toxic gases formed during incomplete combustion and poses a serious threat to both human and animal health. The main pathogenic mechanism of carbon monoxide is associated with its high affinity to hemoglobin, leading to tissue hypoxia. Chronic hypoxia may cause structural and functional alterations in various organs and tissues. However, the effect of carbon monoxide on the female reproductive system, particularly on uterine tissues, remains insufficiently studied. The aim of this study was to investigate morphological and morphometric changes in the uterus under chronic exposure to carbon monoxide in experimental animals.